Metode Tafsir Bil-Ma’tsur Surat An-Naml Ayat 18 dan Implikasinya terhadap Kepemimpinan Islam - Suarna, Dedi; Irfieh, Fauzia (Melati Institute, 2024)
This research examines the tafsir bil-ma'tsur method in Surah An-Naml Verse 18 and its implications for the concept of leadership in Islam. The selection of this topic is motivated by the importance of understanding the valid interpretation and the relevance of the teachings of the Qur'an in the context of leadership, especially in facing contemporary leadership challenges. The research method used is a literature review with the approach of tafsir bil-ma'tsur, which is the interpretation of the Qur'an based on the history of the Prophet Muhammad SAW and his companions. The analysis focused on the interpretation of verse 18 of Surah An-Naml which talks about leadership, as well as its application in the context of managerial and Islamic leadership. The results show that this verse contains leadership principles that include justice, honesty, and wise decision-making, which can be used as guidelines for Muslim leaders in various fields. The implications of this interpretation emphasize the importance of applying Islamic values in effective and responsible leadership practices. This research makes an important contribution to the development of the science of tafsir and leadership management in Islam, as well as a guide for leaders in facing the dynamics of modern society.